Synthesis and Characterization of (2,3-Dimethyl-4-hydroxyphenyl)tellurium(IV) Halides - Verma, K.K.; Garg, Sapana (Asian Journal of Chemistry, 2010)
This paper reports the preparation and properties of (2,3- dimethyl-4-hydroxyphenyl)tellurium(IV)-halides, RnTeX4–n (where X = Cl–, Br –, I– and n = 1,2). Conductance and cryoscopic measurements reveal the molecular nature of RTeCl3 and R2 TeX2 and 1 : 1 electrolyte-type nature of RTeBr3 and RTeI3 in nitrobenzene, nitromethane and acetonitrile. The 1H NMR and IR spectra suggest that the halotellurium groups are in para position to the —OH group. The far IR spectra reflect the polymeric nature of RTeX3 and monomeric nature having a Ψ-trigonal bipyramidal structure of R2TeX2 type compounds.